Pembinaan Guru Dalam Menyusun Administrasi Pembelajaran Melalui Google Drive - Sofianingtyas, Nur (Institut Teknologi Pendidikan Indonesia, 2023)
The purpose of this research is as an alternative strategy to improve teachers' ability to compile learning administration online through coaching conducted by school supervisors using Google Drive. The method used is a literature review and simple observations through a series of activities related to library data collection methods, reading and recording, and managing study materials sourced from books and simple observations from supervisory documents, journal articles, books, and the web. The results of the writing obtained that the teacher coaching strategy by school supervisors is an effort by school supervisors to provide direction and guidance to teachers to improve teachers' knowledge and skills and improve the quality of education in schools, especially in terms of preparing learning administration.